2007
DOI: 10.1111/j.1365-3164.2007.00558.x
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of topical eprinomectin in the treatment ofChorioptessp. infestation in alpacas and llamas

Abstract: Chorioptes sp. mite infestation is increasingly recognized as a cause of skin disease in New World camelids and there is a need for an effective treatment protocol to eliminate herd infestation. In this field trial, eprinomectin applied topically at the rate of 0.5 mg kg(-1) weekly for 10 weeks was found to be ineffective in a herd of 12 llamas and 16 alpacas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
0
25
0
1
Order By: Relevance
“…The three alpacas in this case report had received several applications of eprinomectin without improvement in either the skin or the general condition. In an uncontrolled field study, Plant et al 33 . demonstrated that 10 weekly doses of topical eprinomectin at 0.5 mg kg −1 were ineffective for the eradication of chorioptic mange in llamas and alpacas.…”
Section: Discussionmentioning
confidence: 99%
“…The three alpacas in this case report had received several applications of eprinomectin without improvement in either the skin or the general condition. In an uncontrolled field study, Plant et al 33 . demonstrated that 10 weekly doses of topical eprinomectin at 0.5 mg kg −1 were ineffective for the eradication of chorioptic mange in llamas and alpacas.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a heavy infestation may be free of any symptoms of mange although others in the same herd with lower infestations may show severe extensive skin lesions [20]. Often alopecia and scaling are seen on the feet – often as in sarcoptic mange between the toes and the base of the tail.…”
Section: Mangementioning
confidence: 99%
“…In contrast, Plant et al . () reported that topically applied eprinomectin at a rate of 0.5 mg/kg weekly for 10 weeks was ineffective against chorioptes in a herd of 28 camelids. The presumed variability in absorption of topical eprinomectin across camelid groups may be caused by individual differences in follicle density and dermal thickness of different animals.…”
Section: Introductionmentioning
confidence: 97%
“…Eprinomectin has been previously evaluated as a topical treatment of chorioptic mange in alpacas, although pharmacokinetic analyses are currently lacking (D'Alterio et al ., ; Plant et al ., ). D'Alterio et al .…”
Section: Introductionmentioning
confidence: 99%